2005
DOI: 10.1063/1.1922787
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoresistive magnetometer with improved bandwidth and response characteristics

Abstract: We report on the realization and characterization of a high performance, compact magnetometer based on a magnetoresistive sensor and working in the range ±600 T. The output is provided both numerically and by means of a field-proportional voltage. Spurious offset effects are suppressed by flipping the film magnetization at a frequency of 100 kHz, 2 / 3 orders of magnitude higher than in conventional applications. The design allows for a field resolution of 20 nT, low output noise density, and high precision an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…We have shown that separate processing of the and voltages instead of simple averaging leads to more efficient correction of the crossfield error. This is easy in digital magnetometers such as [11]. However, if field compensation is possible, such processing is not necessary.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that separate processing of the and voltages instead of simple averaging leads to more efficient correction of the crossfield error. This is easy in digital magnetometers such as [11]. However, if field compensation is possible, such processing is not necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The only serious candidates for these applications are AMR sensors and miniaturized fluxgate sensors. While the precision of AMR sensors is limited to 10 nT [1,2], effort is given to develop small-size fluxgate sensors. One path is miniaturization of the classical parallel fluxgate [3][4][5], but the success in this direction is only slow.…”
Section: Introductionmentioning
confidence: 99%
“…The principles of AMR sensors are described in [13], comparative measurements of the noise of various magnetoresistors are shown in [14]. The best AMR sensors have a noise of 200 pT/ [15]; however, it is difficult to achieve pT noise values with the whole AMR magnetometer; realistic resolution is 10 nT [16].…”
Section: Hall Sensorsmentioning
confidence: 99%